AKTUALISASI PENDIDIKAN NILAI DAN MORAL PADA SISWA SEKOLAH DASAR MELALUI MEDIA PEMBELAJARAN BERBASIS PERMAINAN WORDWALL - Triaswari, Finanda Dwi; Sutrisno, Sutrisno; Adiyaksa, Wily; Ayu Rustiya, Sela (EDUPEDIA, 2023)
The purpose of this study was to find out how the model of inculcating value and moral education in  elementary school students through game-based learning media called wordwall. The research method used is qualitative research with a case study approach, using interview and observation instruments. The results of this study describe the moral values of elementary school children that need to be improved again.  At any  level of  education,  especially  basic  education.  Because elementary school  education  is  the  main  foundation  for  Indonesia's young generation. Students are identical with the world of play, so the suitable media is media that contains elements of the game. In line with that, the media that can be used for interactive learning is Wordwall. This website-based application can be used to create learning media such as quizzes, match, pair, word random, word search,  grouping.  This  Wordwall learning media  was  created with the  aim  of providing  knowledge  and  instilling  what  and  how  these  moral  values  are  in elementary school children in everyday life. The method used in this research is observation or survey.  The results of  this study  describe  the  moral values  of elementary school children that need to be improved again.